2017
DOI: 10.3855/jidc.8643
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of plasmid-mediated quinolone resistance and virulence genes in avian Escherichia coli isolates from Algeria

Abstract: Introduction: The emergence and spread of quinolone-resistant Escherichia coli in poultry products puts consumers at risk of exposure to the strains of E. coli that resist antibiotic treatment. The objective of this study was to define the prevalence and virulence potential of poultryassociated nalidixic acid (NAL)-resistant E. coli in the Annaba city, Algeria. Methodology: In total, 33 samples of retail chicken meat were purchased from various butcher shops and examined for bacterial contamination with NAL-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The results of this study showed that the antimicrobial resistance of E. coli isolated from poultry was higher than from beef to the most of tested antibiotics. The high resistance to tetracycline, ampicillin, amoxycillin–clavulanic acid, trimethoprim/sulphamethoxazole and streptomycin in this study was in agreement with previous reports conducted in Egypt [ 10 , 43 ] and Algeria [ 44 ]. While in Spain, most of E. coli isolated from diarrhoeic and healthy lambs were highly resistant to tetracycline and streptomycin but show lower resistance to ampicillin [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed that the antimicrobial resistance of E. coli isolated from poultry was higher than from beef to the most of tested antibiotics. The high resistance to tetracycline, ampicillin, amoxycillin–clavulanic acid, trimethoprim/sulphamethoxazole and streptomycin in this study was in agreement with previous reports conducted in Egypt [ 10 , 43 ] and Algeria [ 44 ]. While in Spain, most of E. coli isolated from diarrhoeic and healthy lambs were highly resistant to tetracycline and streptomycin but show lower resistance to ampicillin [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…In isolated E. coli , qnr A and qnr B detected in 33.3% of isolates, all nalidixic acid and/or ciprofloxacin resistant isolates harboured both genes. While qnr B and qnr S were identified in 10.4% of nalidixic acid resistant E. coli isolated from Algerian retail chicken meat [ 44 ] and in 10.0% of E. coli isolates obtained from bovine carcasses in Mexico [ 58 ]. In contrast, qnr A, qrn B and qrn S genes could not be identified in enrofloxacin-resistant E. coli strains from poultry in Mexico [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these rare studies, Lounis et al [27] have reported, in opposition to our results, that the most prevalent genes in APEC were iutA (90.6%) followed by ompT (86.9%) and iss (85.8%). While Laarem et al [28] detected the presence of 4 isolates (13.8%) of avian E. coli carried one of Shiga toxin E. coli-associated genes stx1, stx2, and ehxA alleles. Likewise, in a recent study in Algeria [29], a set of plasmidic virulence genes (iutA, fyuA, irp2, iroN, fimH, cvaC, traT, iss, sitA, ompT, hlyF, cvaA, etsA, etsB, eitA, and tsh) and chromosomal virulence genes (sitA fyuA, vat, and ibeA) associated with APEC have been detected, paradoxically, in fecal E. coli strains isolated from clinically healthy chickens.…”
Section: Discussionmentioning
confidence: 97%
“…The mcr- 1 gene was found in all isolates that exhibited colistin resistance, demonstrating its role in colistin resistance. Several international studies have investigated the phenotypic resistance profile of E. coli isolates from chicken, such as those conducted in Saudi Arabia [ 23 ], Algeria [ 24 ], China [ 25 ], Canada [ 26 ], and the Netherlands [ 27 ]. Our results showed a high resistance profile to the first-line therapeutic antibiotics that are commonly used in poultry disease treatment like ampicillin and tetracycline [ 28 ].…”
Section: Discussionmentioning
confidence: 99%